Evaluation of current diagnostic methods for COVID-19 - ŞENGÖR, MUSTAFA; GÜNDÜZ, OĞUZHAN (AIP Publishing, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the agent responsible for the coronavirus disease of 2019 (COVID-19), which triggers lung failure, pneumonia, and multi-organ dysfunction. This enveloped, positive sense and single-stranded RNA virus can be transmitted through aerosol droplets, direct and indirect contacts. Thus, SARS-CoV-2 is highly contagious and has reached a pandemic level in a few months. Since COVID-19 has caused numerous human casualties and severe economic loss posing a global threat, the development of readily available, accurate, fast, and cost-effective diagnostic techniques in hospitals and in any places where humans spread the virus is urgently required. COVID-19 can be diagnosed by clinical findings and several laboratory tests. These tests may include virus isolation, nucleic acid-based molecular assays like real-time polymerase chain reactions, antigen or antibody-based immunological assays such as rapid immunochromatographic tests, enzyme-linked immunosorbent assays, immunofluorescence techniques, and indirect fluorescent antibody techniques, electrochemical sensors, etc. However, current methods should be developed by novel approaches for sensitive, specific, and accurate diagnosis of COVID-19 cases to control and prevent this outbreak. Thus, this review will cover an overview and comparison of multiple reports and commercially available kits that include molecular tests, immunoassays, and sensor-based diagnostic methods for diagnosis of COVID-19. The pros and cons of these methods and future perspectives will be thoroughly evaluated and discussed.
Keywords: RAPID DETECTION; VIRUS; SARS; CORONAVIRUSES; HYBRIDIZATION; TRANSCRIPTION; MICROARRAY; IDENTIFICATION; OUTBREAK; ASSAYS